Vol.3 - Lewis, Thomas Tandy (ed.) ("Pasadena,California", 2007)
U.S. Supreme Court Records and Briefs, 1832-1978 contains the world's most comprehensive collection of records and briefs brought before the nation's highest court by leading legal practitioners - many who later became judges and associates of the court.This book contains the official US Supreme Court Transcript of Record for this case. This book does not contain the Court's opinion or any filings in this case. The below data was compiled from various identification fields in the bibliographic record of this title.
Volume3 ScottV. sandford- Zoning appendixes indexes
Keywords: United States-Supreme court-History